BEHCET’S DISEASE PRESENTING WITH LIFE THREATENING MANIFESTATION OF CEREBRAL VENOUS THROMBOSIS - Naveed, Ushna; Iqbal, Aneela; Ain, Qurrat-Ul; Hamdani, Muhammad Afzal; Abid Butt, Mujeeb-ur-rehman; Ashraf, Muhammad Atif (Journal of Ayub Medical College Abbottabad, 2020)
Behcet’s disease (BD) presents as uncommon inflammatory disorder involving multiple systems, identified by longstanding relapsing path. Its chief manifestations are oral and genital ulcers together with involvement of the eyes, skin and joints. Neurological and vascular complications are significant. We report a case of a twenty-four years old young male who presented with headache, fever, and vomiting along with decreased vision; and repeated oral and genital ulcers. Diagnosis of BD complicated with cerebral venous thrombosis (CVT) was made. He was treated with corticosteroids, immunosuppression therapy and colchicine along with anticoagulation therapy. He responded well to the given treatment. Cerebral venous thrombosis complications in with BD can lead to serious consequences. Early recognition and treatment may lessen poor outcomes. Keywords: Behcet’s disease; Life threatening manifestation; Cerebral venous thrombosis